Complexation of arsenite with dissolved organic matter: Conditional distribution coefficients and apparent stability constants - Liu, Guangliang; Cai, Yong (Chemosphere (Oxford), 2010)
The complexation of arsenic (As) with dissolved organic matter (DOM), although playing an important role in regulating As mobility and transformation, is poorly characterized, as evidenced by scarce reporting of fundamental parameters of As–DOM complexes. The complexation of arsenite (As III) with Aldrich humic acid (HA) at different pHs was characterized using a recently developed analytical technique to measure both free and DOM-bound As. Conditional distribution coefficient ( K D ), describing capacity of DOM in binding As III from the mass perspective, and apparent stability constant ( K s ), describing stability of resulting As III–DOM complexes, were calculated to characterize As III–DOM complexation. Log K D of As III ranged from 3.7 to 2.2 (decreasing with increase of As/DOM ratio) at pH 5.2, from 3.6 to 2.6 at pH 7, and from 4.3 to 3.2 at pH = 9.3, respectively. Two-site ligand binding models can capture the heterogeneity of binding sites and be used to calculate K s by classifying the binding sites into strong (S1) and weak (S2) groups. Log K s for S1 sites are 7.0, 6.5, and 5.9 for pH 5.2, 7, and 9.3, respectively, which are approximately 1–2 orders of magnitude higher than for weak S2 sites. The results suggest that As III complexation with DOM increases with pH, as evidenced by significant spikes in concentrations of DOM-bound As III and in K D values at pH 9.3. In contrary to K D , log K s decreased with pH, in particular for S1 sites, probably due to the presence of negatively charged H 2 AsO 3 - and the involvement of metal-bridged As III–DOM complexation at pH 9.3.